2019
DOI: 10.1101/510008
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enjoy The Violence: Is appreciation for extreme music the result of cognitive control over the threat response system?

Abstract: Traditional neurobiological theories of musical emotions explain well why extreme music such as punk, hardcore or metal, whose vocal and instrumental characteristics share much similarity with acoustic threat signals, should evoke unpleasant feelings for a large proportion of listeners. Why it doesn't for metal music fans, however, remains a theoretical challenge: metal fans may differ from non-fans in how they process acoustic threat signals at the subcortical level, showing deactivated or reconditioned respo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…It is in fact likely that such context effects affect appraisals of roughness for all types of sounds [48], allowing e.g. a rough shout to be perceived as a positive bout of laughter [14], or rough music as pleasingly empowering [7]. Tools like ANGUS, which allow to control cues of vocal arousal at the stimulus level, contribute to make possible more research on how these cues are cognitively appraised in ecological situations [38].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is in fact likely that such context effects affect appraisals of roughness for all types of sounds [48], allowing e.g. a rough shout to be perceived as a positive bout of laughter [14], or rough music as pleasingly empowering [7]. Tools like ANGUS, which allow to control cues of vocal arousal at the stimulus level, contribute to make possible more research on how these cues are cognitively appraised in ecological situations [38].…”
Section: Discussionmentioning
confidence: 99%
“…There is a vast biological literature suggesting that roughness is a signal of threat and negative salience throughout the human and animal communicative repertoire [32][33][34]. In addition, these signals, shaped by biological evolution, have also been selected for in cultural artefacts, such as musical sounds and sound alarms, which aim at the same effect [7,35]. In [36], musical sequences transformed with distortion were evaluated as more negative and aroused than non-transformed sequences; in [5], so were musical instrument samples and alarm sounds when manipulated with 40-60Hz temporal modulations.…”
Section: Study 4: Effect On Non-vocal Stimulimentioning
confidence: 99%
See 1 more Smart Citation
“…A lot of heavy metal music is perceived as violent and aggressive, and is consistent with auditory threat signals (Ollivier et al 2019), so there has been a continual association between heavy metal and immoral or violent behavior, but that connection is largely unfounded. Rather, it has been found that heavy metal, including with violent themes, consistently has positive emotional, cognitive, and social consequences for fans (Messick 2020;Olsen et al 2020;Sharman and Dingle 2015;Leisuk 2010;McFerran et al 2015).…”
Section: Mood and Symptom Maintenancementioning
confidence: 99%
“…With a cumulated 4,000 citations since 2001 (bibliometric data based on a search using Google Scholar on January 16, 2019), these four studies (2-5) have had a remarkable influence on the neuroscience literature, and on the music neuroscience community in particular, for which the 2001 study can be considered one of the founding acts: Of these citations, 1,770 (44%) include the words "music" or "musical" in their titles. While the question of the musical expression of emotion has a long history of investigation, including in PNAS (6), and the 1990s psychophysiological strand of research had already established that musical pleasure could activate the autonomic nervous system (7), the authors' demonstration of the implication of the reward system in musical emotions was taken as inaugural proof that these were veridical emotions whose study has full legitimacy to inform the neurobiology of our everyday cognitive, social, and affective 1, linking the auditory and orbitofrontal cortices to the NAcc, and (B) one of the many possible mechanisms of musical emotion induction discussed in the literature, hypothetically linking the auditory thalami, the amygdala, and the dorsolateral prefrontal cortex engaged, for example, when experiencing heavy metal (14). As of yet, it is unclear how mechanisms such as these relate to one another.…”
mentioning
confidence: 99%